Students’ Self-Regulated in Learning Mathematics using Realistic Mathematical Education Model - Rama Nida Siregar; Didi Suryadi; Sufyani Prabawanto; Abdul Mujib (IKIP Siliwangi, 2022)
To study at school, students must have soft skills such as self-regulated learning, namely the ability of students to manage their own learning. The significance of students' self-regulated learning is what inspired this study. This study sought to ascertain the rise in students' self-regulated learning when learning mathematics using a realistic mathematics education model, as well as the students' reactions to learning mathematics using a realistic mathematics education model. This kind of study uses questionnaire analysis to do descriptive research. A self- regulated learning questionnaire and a questionnaire for students' responses made up the tool used to assess the self-regulated learning abilities that had been put to the test. Data were collected for this study to examine the rise in realistic mathematics education students' ability to learn mathematics independently, as well as the students' attitudes toward learning mathematics through mathematics education, which were assessed using a Likert attitude scale. The self-regulated learning scale is made up of four parts: the students' evaluations of how well they (1) use and locate pertinent learning resources in mathematics, (2) select and determine their learning strategies in mathematics, (3) assess and evaluate their learning outcomes in mathematics, and (4) have a positive view of themselves as mathematicians. By utilizing realistic mathematics education, the findings of this study about self-regulated learning in mathematics can be viewed as a whole. Based on the results of data analysis it is known that students' responses to realistic mathematics education models are positive which are adapted to real-life contexts or everyday life which will arouse students' self-regulated learning in solving problems because they are related to real life. This demonstrates that 98.18% of students respond positively.